El Cordero de Dios. Consideración teológica sobre el Misterio Pascual de Jesucristo - Ledesma LC, Juan Pablo (Alpha Omega, 2012)
In his humanity, Jesus Christ lived according to the Jewish traditions of his time. However, apparently, he celebrated the Passover without a lamb and apart from the temple. In reality, he was himself the true Lamb and the Temple. He sacrificed his own life during the Passover as a perfectly efficacious offering, whereby he robbed death of its sting. He is the Lamb slain, yet still living, whose resurrected Body nourishes the Church in the Eucharistic feast.